Sodium bicarbonate nanoparticles modulate the tumor pH and enhance the cellular uptake of doxorubicin - Abumanhal-Masarweh, Hanan (J Control Release, 2019)
Acidic pH in the tumor microenvironment is associated with cancer metabolism and creates a physiological barrier that prevents from drugs to penetrate cells. Specifically, ionizable weak-base drugs, such as doxorubicin, freely permeate membranes in their uncharged form, however, in the acidic tumor microenvironment these drugs become charged and their cellular permeability is retarded. In this study, 100-nm liposomes loaded with sodium bicarbonate were used as adjuvants to elevate the tumor pH. Combined treatment of triple-negative breast cancer cells (4T1) with doxorubicin and sodium-bicarbonate enhanced drug uptake and increased its anti-cancer activity. In vivo, mice bearing orthotropic 4T1 breast cancer tumors were administered either liposomal or free bicarbonate intravenously. 3.7±0.3% of the injected liposomal dose was detected in the tumor after twenty-four hours, compared to 0.17%±0.04% in the group injected free non-liposomal bicarbonate, a 21-fold increase. Analyzing nanoparticle biodistribution within the tumor tissue revealed that 93% of the PEGylated liposomes accumulated in the extracellular matrix, while 7% were detected intracellularly. Mice administered bicarbonate-loaded liposomes reached an intra-tumor pH value of 7.38±0.04. Treating tumors with liposomal bicarbonate combined with a sub-therapeutic dose of doxorubicin achieved an improved therapeutic outcome, compared to mice treated with doxorubicin or bicarbonate alone. Interestingly, analysis of the tumor microenvironment demonstrated an increase in immune cell’ population (T-cell, B-cell and macrophages) in tumors treated with liposomal bicarbonate. This study demonstrates that targeting metabolic adjuvants with nanoparticles to the tumor microenvironment can enhance anticancer drug activity and improve treatment.